Alcohol Intake in Early Pregnancy and Spontaneous Preterm Birth: A Cohort Study. (26th December 2019) - Weile, Louise Katrine Kjær; Hegaard, Hanne Kirstine; Wu, Chunsen; Tabor, Ann; Wolf, Hanne Trap; Kesmodel, Ulrik Schiøler; Henriksen, Tine Brink; Nohr, Ellen Aagaard
Abstract : Background: Limited research has addressed whether maternal alcohol intake in early pregnancy increases the risk of spontaneous preterm birth. In the current study, we examined how alcohol binge drinking and weekly alcohol intake in early pregnancy were associated with spontaneous preterm birth in a contemporary cohort of Danish women. Methods: We included 15, 776 pregnancies of 14, 894 women referred to antenatal care at Copenhagen University Hospital, Denmark, between 2012 and 2016. Self‐reported alcohol intake in early pregnancy was obtained from a Web‐based questionnaire completed prior to the women's first visit at the department. Information on spontaneous preterm birth was extracted from the Danish Medical Birth Register. Adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) of spontaneous preterm birth according to self‐reported alcohol binge drinking and weekly intake of alcohol in early pregnancy were derived from Cox regression. Results: Women reporting 1, 2, and ≥ 3 binge drinking episodes had an aHR for spontaneous preterm birth of 0.88 (95% CI 0.68 to 1.14), 1.34 (95% CI 0.98 to 1.82), and 0.93 (95% CI 0.62 to 1.41), respectively, compared to women with no binge drinking episodes. Women who reported an intake of ≥ 1 drink per week on average had an aHR for spontaneous preterm birth of 1.09 (95% CI 0.63 to 1.89) compared to abstainers. When restricting to nulliparous women or cohabiting women with ≥ 3 years of higher education, this estimate was 1.28 (95% CI 0.69 to 2.40) and 1.20 (95% CI 0.67 to 2.15), respectively. Conclusion: We found no evidence that maternal alcohol intake in early pregnancy was associated with a higher risk of spontaneous preterm birth, neither for alcohol binge drinking nor for a low average weekly intake of alcohol.